Mensuração das dimensões cardíacas pelo método VHS (Vertebral Heart Size) em cães - Inamassu, Letícia Rocha [UNESP] (2011)
It is imortant to be able to evaluate the cardiact size . In 1995, was proposed by Buchanan and Bücheler a new way to measure the dimensions of the cardiac silhouette. This study aims to gather several studies of the cardiac dimensions by VHS method in the right lateral recumbency of of different breeds of dogs in a single work, facilitating the assess to information. Deep chest breeds have a smaller mean VHS value than the barrel chest breeds, showing that there is a variation of the VHS values acoording to the thoracic conformation of each breed, which indicates that there is a need to recognize the specific VHS values according to the breed standard to not to interpret the cardiac measurement in a wrong way through not compatible reference values for the animal. There is the individual variation that should be taken into accont at the time of measurement. The VHS is a helper method to a radiographic evaluation of the heart, and the ultrasonography remains the gold standard for the evaluation of the cardiac chambers and other changes of the heart